Bringing ABA into Early Childhood Routines to Meet the Needs of Young Children with ASD - Leach, Debra (Journal of the American Academy of Special Education Professionals, 2014)
It is well documented that applied behavior analysis (ABA) approaches to intervention for young children with ASD have a strong evidence-base. Although federal special education law mandates that early intervention services and supports be implemented within the natural environment to the maximum extent appropriate, many young children with ASD still receive ABA interventions in clinical and therapeutic settings and contexts. This article discusses the value of using ABA interventions with the contexts of everyday home, school, and community routines with young children with ASD through the use of routines-based interventions (RBI) and provides guidelines for doing so.